Friends, food or worth fighting for? A proposed stereotype content model for nonhuman animals - Paul V. Patinadan; Denise B. Dillon (Human-Animal Interactions, 2022)
Abstract The human perception of nonhuman animals is a burgeoning area of anthrozoology, with the past decade seeing an increase in work within the field. This study attempted to assess people’s social perceptions about various nonhuman animals. Food animals, for example, have often been classified as being less sentient and have been historically devoid of rights and moral concern due to their nature as a consumable commodity. Advancements in social psychology have allowed the general hypothesis that some key theories might be transferrable toward understanding how people perceive animals. This study borrows from work on the Stereotype Content Model (SCM) and attempts to replicate the social perceptions of animals along the warmth-competence dimensions among a Singaporean sample (N = 325) of vegetarians, animal activists, and those who regarded themselves as neither. Ratings on the scales of warmth and competence for 16 animals were subjected to multidimensional scaling analysis. Results indicate people hold different social perceptions congruent to the various animal species. Four main clusters were identified, and these were named, ‘Love’, ‘Save’, ‘Indifferent’, and ‘Dislike’ based on the expectancy of how participants might feel toward the animals. The ethical ideology of participants was also measured, with vegetarians and animal activists holding more ‘absolutist’ beliefs. When factored into the scaling process, ethical ideology had little impact on participants’ social perceptions of nonhuman animals.